2014
DOI: 10.1093/eurpub/cku166.071
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Cost-Effectiveness of the Mediterranean Diet: Results of a Systematic Review

Abstract: Abstract:The growing impact of chronic degenerative pathologies (such as cardiovascular disease, type 2 diabetes and Alzheimer's disease) requires and pushes towards the development of new preventive strategies to reduce the incidence and prevalence of these diseases. Lifestyle changes, especially related to the Mediterranean diet, have the potential to modify disease outcomes and ultimately costs related to their management. The objective of the study was to perform a systematic review of the scientific liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Previous studies have reviewed or evaluated the cost effectiveness 67,68 and potential health care savings 13,14 associated with a Mediterranean-style diet. The health outcomes included in these reviews and analyses were limited to heart disease end points and only one considered health care costs in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reviewed or evaluated the cost effectiveness 67,68 and potential health care savings 13,14 associated with a Mediterranean-style diet. The health outcomes included in these reviews and analyses were limited to heart disease end points and only one considered health care costs in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of the Mediterranean diet is estimated to be rather rational for a middle-income household in Greece (Vlismas et al 2010), which might be not the case for families in low SES areas. Concerning the adherence to the Mediterranean diet, Mediterranean societies are rapidly withdrawing from this eating pattern, mainly due to influence from the Western diet patterns and the increasing prices of some of main Mediterranean diets' food items (Saulle et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of economic analyses drew on eight studies, three of which looked at healthcare cost savings 28. One of these found that the Mediterranean diet was highly cost-effective for increasing quality adjusted life years after a first myocardial infarction.…”
Section: Mediterranean Dietmentioning
confidence: 99%
“…A primary prevention study found lower healthcare costs in adults following the diet, who gained an average six life-years that were lost to disability in those not following the diet. Another study in the review found a cost-effectiveness ratio of £1,300 per non-fatal myocardial infarction avoided 28. Five studies in the review looked at the costs of the diet, compared with a traditional Western diet.…”
Section: Mediterranean Dietmentioning
confidence: 99%